Ocular mucoadhesive and biodegradable spanlastics loaded cationic spongy insert for enhancing and sustaining the anti-inflammatory effect of prednisolone Na phosphate; Preparation, I-optimal optimization, and In-vivo evaluation - Mayada Said; Khaled M. Ali; Munerah M. Alfadhel; Obaid Afzal; Basmah Nasser Aldosari; Maha Alsunbul; Rawan Bafail; Randa Mohammed Zaki (Elsevier, 2024)
This study aimed to formulate and statistically optimize spanlastics loaded spongy insert (SPLs-SI) of prednisolone Na phosphate (PRED) to enhance and sustain its anti-inflammatory effect in a controlled manner. An I-optimal optimization was employed using Design-Expert® software. The formulation variables were sonication time, the Span 60: EA ratio and type of edge activator (Tween 80 or PVA) while Entrapment efficiency (EE%), Vesicles' size (VS) and Zeta potential (ZP) were set as the dependent responses. This resulted in an optimum spanlastics (SPLs) formulation with a desirability of 0.919. It had a Span60:Tween80 ratio of 6:1 with a sonication time of 9.5 min. It was evaluated in terms of its EE%, VS, ZP, release behavior in comparison to drug solution in addition to the effect of aging on its characteristics. It had EE% of 87.56, VS of 152.2 nm and ZP of −37.38 Mv. It showed sustained release behavior of PRED in comparison to drug solution with good stability for thirty days. TEM images of the optimized PRED SPLs formulation showed spherical non-aggregated nanovesicles. Then it was loaded into chitosan spongy insert and evaluated in terms of its visual appearance, pH and mucoadhesion properties. It showed good mucoadhesive properties and pH in the safe ocular region. The FTIR, DSC and XRD spectra showed that PRED was successfully entrapped inside the SPLs vesicles. It was then exposed to an in-vivo studies where it was capable of enhancing the anti-inflammatory effect of PRED in a sustained manner with once daily application compared to commercial PRED solution. The spongy insert has the potential to be a promising carrier for the ocular delivery of PRED.